Efficiency of thermal relaxation by radiative processes in protoplanetary discs: constraints on hydrodynamic turbulence - Malygin, Mykola G.; Dullemond, Cornelis (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
Gesehen am 13.09.2017